(3EfHGA GdZeQ HCHfGA GdYeQs - (3CMeO Hf Ydj Hf eMeO GdcfGfj GdYSbdGfj, CHh GdaVd, TgGH GdOjf, GHf nMnLQ,J (B852 (3g` s
(3ChdgG (B:s
(3GeG HYO gPG JYdjb LeYJ ajg MhGOK GdReGf GdPi COQcJg efP ehdOi SfI (B773 (3hgde LQG , heaUdG ai cd SfI Yf hajGJ GdCYjGf eSJhYHkG dQhGI GdMOjK NUhUkG ef dbjJg hCLGRdi s
(3BNQgG (B:s
(3jfJgi Edi JQLeI jHZG GdXGgQi s
(3fSNI KGdKIs
(3fSNI LRAGf ai eLdOGfs
(3cd LRA HNW jNGda GdBNQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B173s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B68 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B16 s
Keywords: (3GdJGQjNs